One hundred and fifty years of Mute Swans on the Thames - Cramp, Stanley (Wildfowl, 1972)
Counts of Mute Swans Cygnus olor made from 1823 to 1972 on the annual swan-upping expeditions on the Thames between central London and Henley-on-Thames are given and the trends illustrated by graphs based on three-year moving averages. For much of the 150 years the total numbers of swans varied between 400 and 600, rising above this briefly in the late 1850's, with a more striking increase to over 1,000 birds in the 1950's, followed by an almost equally rapid fall. The numbers of adults with young tended to vary between 50 and 100 until the late 1920's, rising above 100 until about 1950, thereafter declining markedly. Possible reasons for some of these fluctuations are discussed.